Scalable fabrication of graphene-based laminate membranes for liquid and gas separations by crosslinking-induced gelation and doctor-blade casting - Yang, Euntae (2021)
Graphene-based laminate membranes have recently demonstrated unique advantages over the traditional separation membranes made of polymers or ceramics. For both gas and liquid separations, various designs of crosslinker-stabilized graphene oxide (GO) membranes have been reported. However, the preparation methods used for those are poorly scalable for industrial applications. Herein, we report the fabrication of large-area (1333 cm2) GO-based membranes via doctor-blade casting of gel-like slurries prepared by incorporating calcium ions (Ca2+), ferric ions (Fe3+), polyethylene oxide (PEO), or polyethyleneimine (PEI) as crosslinkers. We found that all crosslinkers tested are suitable for the gelation of dilute GO dispersions (1–5 mg/mL) for doctor-blade casting. Besides, all crosslinked-GO membranes demonstrated outstanding stability under sonication compared to a GO-only membrane prepared via vacuum-assisted filtration. In aqueous nanofiltration tests, Fe3+-crosslinked GO membranes achieved virtually complete rejection of different organic dyes. PEO-crosslinked GO membranes, on the other hand, exhibited an outstanding performance for the separation of carbon dioxide (CO2) and nitrogen (N2) gases with a CO2/N2 selectivity of 52. Given the scaleup potential of doctor-blade casting and the practicality of crosslinking-based gelation approach, the proposed approach is promising to increase the industrial relevance of GO-based laminate membranes.